Method and tool to generate requirement traceability Matrix for scrum development methodology - Duraisamy, Gunavathi (2014)
Requirement traceability matrix is a table that captures the complete user and system requirement for a system. It helps to trace from requirement till testing in order to verify that the requirement is fulfilled. In SCRUM development methodology, requirement traceability matrix is used to capture the linkage of user stories between product backlog and sprint backlog documents. The linkages between the requirements are retrieved through these two documents. However, unstructured format of both documents do not help in requirement traceability. Thus, requirement traceability has become an issue for SCRUM practitioners especially for system development and maintenance phases. Therefore, this study introduce structured format of available artifacts which can create and maintain traceability link between those documents and develops a tracing tool to generate requirement traceability matrix automatically. Both the documents used in this study have to be prepared by using the proposed structured format and the developed traceability tool is able to generate the requirement traceability matrix automatically. Two case studies have been used for pre-test and post-test experiments. The result shows that the introduced structured format is very useful and it has increased the efficiency of retrieving the matrix far better than manual process. By using the proposed method and tool, it’s statistically shows significant result of time saving, completeness and correctness to generate requirement traceability matrix. Thus, the proposed method and the developed tool help in achieving requirement traceability in SCRUM methodology.